The Effect of Musculoskeletal Fatigue on Postural Control in Patients with Long Term mTBI - Mallett, John Carlo (My University, 2024)
Purpose This study aims to investigate the effects of fatigue on postural control in individuals with a previous mild traumatic brain injury (mTBI). Previous research shows an increased risk of musculoskeletal injury in individuals with a history of concussion, as well as a change in postural control dynamics among concussed individuals. This research was conducted to explore the interaction between concussion status and fatigue on postural control variables. Methods Participants included nine individuals with recent concussions (within the past 13 months) and 13 healthy controls. All completed a virtual reality (VR) Go/No-Go task while standing on a force plate. Data were collected for center of pressure (CoP) variables including velocity, acceleration, approximate entropy, displacement, and ellipse area. After initial testing, participants completed the Buffalo Concussion Treadmill Test to volitional fatigue, after which they repeated the VR task. A 2x2 ANOVA assessed the effects of fatigue, concussion status, and their interaction on postural control metrics. Results The findings suggest large differences in postural control between concussed and healthy participants across multiple measures with a high variability between participants. Concussed individuals consistently exhibited higher velocity, acceleration, and displacement in both movement directions compared to healthy participants, both before and after the fatigue condition. Similarly, the concussed group demonstrated a larger ellipse area, indicative of increased sway as well as changes in approximate entropy reflected in lower entropy values compared to the healthy group. Discussion While the 2x2 Anova performed revealed little conventional significance, large effect sizes of the concussed condition were observed across nearly all variables. This suggests a high level of variability in the postural control patterns between participants, especially in the concussed condition. Overall, the findings suggest increased sway and less adaptable movement patterns in concussed participants. While sway generally increased after fatigue in concussed participants, the lower adaptability shown by approximate entropy was still lower than healthy participants. Future studies should consider focusing on specific populations with a similar age, concussion severity, and demographic background to eliminate extraneous variables.
Keywords: postural control, mTBI, concussion, musculoskeletal fatigue, force plate